Diari (1800-1808) - Martucci, Vittorio (ed.) (I Quaderni del Lab, 2014)
Like many young Neapolitan physicians, Giosuè Sangiovanni (1776-1849) was involved in the revolution of 1799. He served in the Guard of the Republic, whose tragic end marked his destiny as an exile and a scientist. Sangiovanni keeps track of this experience in his Diaries (1800-1808), hitherto unpublished, where he notes in a fast and sometimes syncopated way the record of his wanderings in Italy, France, Switzerland, Tyrol, Piedmont. There we find not only places, meetings, small events and daily life's adventures - almost the backbone of the autobiography of an Neapolitan exile - but above all the story of an educational trip. In Paris, thanks to his contact with prominent naturalists of the time, such as Cuvier, Lamarck, Saint-Hilaire, Lacépède, this pupil of Domenico Cirillo's reaches his scientific maturity and his academic recognition. Sangiovanni's Diaries end with his final return to Naples, where he, now an advocate of Lamarck's evolutionary theory, was appointed professor of the first chair of Comparative Anatomy in Italy.